2011
DOI: 10.1128/cvi.05299-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Gamma Interferon Release Assays and Tuberculin Skin Testing for Tuberculosis Screening in a Cohort of Patients with Rheumatic Diseases Starting Anti-Tumor Necrosis Factor Therapy

Abstract: Gamma interferon release assays (IGRAs) are increasingly used for latent Mycobacterium tuberculosis infection (LTBI) screening in patients with rheumatic diseases starting anti-tumor necrosis factor (anti-TNF) therapies. We compared the performances of two IGRAs, an enzyme-linked immunospot release assay (T-SPOT.TB) and an enzyme-linked immunosorbent assay (QuantiFERON-TB Gold In Tube [QFT-GIT]), to that of tuberculin skin testing (TST) for LTBI screening of 157 consecutive rheumatic patients starting anti-TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 26 publications
6
34
2
5
Order By: Relevance
“…Overall, our results are in general agreement with previous studies that have examined rates of indeterminate tests and observed rates as low as 1.3-13.4% (20)(21)(22)(23). The indeterminate rates differ between studies and may reflect the nature of the study population (i.e., variable activity of underlying rheumatic disease), geographic origin, sample size, and standards of concomitant immunosuppressive therapy use.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, our results are in general agreement with previous studies that have examined rates of indeterminate tests and observed rates as low as 1.3-13.4% (20)(21)(22)(23). The indeterminate rates differ between studies and may reflect the nature of the study population (i.e., variable activity of underlying rheumatic disease), geographic origin, sample size, and standards of concomitant immunosuppressive therapy use.…”
Section: Discussionsupporting
confidence: 91%
“…It has been demonstrated that IGRAs are superior to TST in identifying LTBI in immunosuppressed and BCG-vaccinated populations (14)(15)(16)(17)20). In this study, we found that the T-SPOT.TBpositive rate was slightly higher than the TST-positive rate (46.5% versus 37.6%) in patients with rheumatic diseases before biologics treatment, which may indicate higher sensitivity in immunosuppressed patients.…”
Section: Discussionmentioning
confidence: 46%
“…Istotną kwestią, która pozostaje do wyjaśnienia, jest pytanie, czy testy IGRA należy stosować zamiast, czy w połączeniu z próbą tuberkulinową. W róż-nych krajach proponuje się odmienne wytyczne [6,7,21,22].…”
Section: Omówienieunclassified
“…W Hiszpanii, Wielkiej Brytanii, Kanadzie i we Włoszech preferuje się strategię diagnostyki LTBI dwuetapowo: wstępne badanie TST, po nim dopiero IGRA, w przypadkach gdy TST jest dodatnie. We Francji TST i IGRA stosuje się natomiast wymiennie [7,21,22]. Australijskie wytyczne nie oferują żadnego konkretnego zalecenia do stosowania testów IGRA, niektórzy proponują wykonanie testu IGRA po negatywnym wyniku próby tuberkulinowej, inni zastępują TST testami IGRA [6].…”
Section: Kontrola Negatywnaunclassified